Genotype‐by‐environment interactions drive the maintenance of genetic variation in a Salmo trutta L. hybrid zone. (30th October 2021) - Folio, Dorinda Marie; Gil, Jordi; Caudron, Arnaud; Labonne, Jacques
Abstract: Allopatric gene pools can evolve in different directions through adaptive and nonadaptive processes and are therefore a source of intraspecific diversity. The connection of these previously isolated gene pools through human intervention can lead to intraspecific diversity loss, through extirpation of native populations or hybridization. However, the mechanisms leading to these situations are not always explicitly documented and are thus rarely used to manage intraspecific diversity. In particular, genotype‐by‐environment (GxE) interactions can drive postzygotic reproductive isolation mechanisms that may result in a mosaic of diversity patterns, depending on the local environment. We test this hypothesis using a salmonid species ( Salmo trutta ) in the Mediterranean (MED) area, where intensive stocking from non‐native Atlantic (ATL) origins has led to various outcomes of hybridization with the native MED lineage, going from MED resilience to total extirpation via full hybridization. We investigate patterns of offspring survival at egg stage in natural environments, based on parental genotypes in interaction with river temperature, to detect potential GxE interactions. Our results show a strong influence of maternal GxE interaction on embryonic survival, mediated by maternal effect through egg size, and a weak influence of paternal GxE interaction. In particular, when egg size is large and temperature is cold, the survival rate of offspring originating from MED females is three times higher than that of ATL females' offspring. Because river temperatures show contrast at small scale, this cold adaptation for MED females' offspring constitutes a potent postzygotic mechanism to explain small‐scale spatial heterogeneity in diversity observed in MED areas where ATL fish have been stocked. It also indicates that management efforts could be specifically targeted at the environments that actively favor native intraspecific diversity through eco‐evolutionary processes such as postzygotic selection.